37. A STUDY ON INSOMNIA CHARACTERISTICS IN STROKE PATIENTS DURING THE EARLY RECOVERY PHASE (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to investigate the characteristics of insomnia patterns (thất miên) in stroke patients during the early recovery phase, thereby providing a basis for individualized diagnosis and integrated treatment approaches.Methods: A cross-sectional study was conducted on 384 stroke patients who met the inclusion criteria at four hospitals in Ho Chi Minh City from October 2024 to June 2025. Data were collected through face-to-face interviews and analyzed using Stata 14 software.Results: Difficulty initiating sleep (91.93%) and light, non-restorative sleep (84.64%) were the most common symptoms of insomnia in post-stroke patients during early recovery. The three most prevalent traditional insomnia syndromes were: Heart-Spleen deficiency (52.86%), Liver Qi stagnation transforming into fire (33.07%), and Yin deficiency with hyperactive fire (28.65%). Most patients presented with a single syndrome (50%); however, 23.44% had overlapping syndromes. Comorbidity analysis revealed a strong positive correlation between Yin deficiency with hyperactive fire and Disharmony between Heart and Kidney.Conclusion: The main insomnia characteristics in stroke patients during early recovery include difficulty falling asleep and non-restorative sleep. Among the traditional syndromes, dual deficiency of the Heart and Spleen was the most prevalent.
Keywords: insomnia, stroke, the early recovery phase, traditional medicine.